1992
DOI: 10.1530/jrf.0.0960549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical restriction of growth of the testicular artery on testis size and histology in bulls

Abstract: The growth of the testicular artery was restricted on one side in young bulls and subsequent testicular development was monitored. After the animals had been killed, the testes were studied histologically and compared with testes from hypoplastic bulls. The growth rate of testes from the experimental side was significantly lower than that of testes from the sham-operated side over a period of 578 days. At death, the experimental testes had a mean (+/- SD) mass of 76 (+/- 41) g compared with 220 (+/- 31) g for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…Studies to date have commonly evaluated testicular echogenicity and heterogeneity, and testicular artery blood flow (Moxon et al., ; Souza et al., ; Zelli et al., ), and found relations with semen quality. The findings are perhaps not surprising because previous work has shown that testicular parenchymal pixel intensity is associated histologically with seminiferous tubule height, the proportion of tubules with a lumen and the size of the lumen (Evans et al., ; Giffin, Franks, Rodriguez‐Sosa, Hahnel, & Bartlewski, ), and because blood flow through the testicular artery is related to the rate of spermatogenesis (Kay, Grobbelaar, & Hattingh, ). Interestingly, in the present study, we found a relationship between mean testicular echogenicity and future semen quality in that higher testicular echogenicity at the tissue level was associated with increased mean normal forward progressive motility in the subsequent monitoring period; findings somewhat similar to those seen in the bull (Arteaga et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…Studies to date have commonly evaluated testicular echogenicity and heterogeneity, and testicular artery blood flow (Moxon et al., ; Souza et al., ; Zelli et al., ), and found relations with semen quality. The findings are perhaps not surprising because previous work has shown that testicular parenchymal pixel intensity is associated histologically with seminiferous tubule height, the proportion of tubules with a lumen and the size of the lumen (Evans et al., ; Giffin, Franks, Rodriguez‐Sosa, Hahnel, & Bartlewski, ), and because blood flow through the testicular artery is related to the rate of spermatogenesis (Kay, Grobbelaar, & Hattingh, ). Interestingly, in the present study, we found a relationship between mean testicular echogenicity and future semen quality in that higher testicular echogenicity at the tissue level was associated with increased mean normal forward progressive motility in the subsequent monitoring period; findings somewhat similar to those seen in the bull (Arteaga et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…A reduction in the blood flow through the testis leads to ischaemia and damage. In an experimental study monitoring the effect of surgical restriction of growth of the testicular artery on testis size and histology in bulls, Kay et al [7] reported that in the artery-restricted testes, spermatogenesis was either totally absent or present in only a small proportion of tubules. They also found that the interstitial tissue accounted for a significantly greater proportion of the testicular tissue than in the sham-operated testes.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, constriction could impair normal blood flow to or from the testis. In previous studies, a reduced arterial supply has been associated with a reduction in the testicular mass and the spermatozoa count in the ejaculates (Love et al 1991;Kay et al 1992;Pinggera et al 2008). By contrast, a reduction in the venous return is associated with venous stasis, hydrocele and varicocele, which may lead to impair the testicular thermoregulation.…”
Section: Discussionmentioning
confidence: 94%